Feasibility of biomass waste as feedstock for a small-scale biomass power plant in a rural area - Yuli Purwanto; Anak Agung Putu Susastriawan; Suparni Setyowati Rahayu; Akanksha Mathur; Nalendra Bagaskara Kaylana; Ricko Dwi Saputro; Muhammad Banu Taslim; Sigit Prasetyo; Mutiara Damaris Panjaitan (Journal of Engineering and Applied Technology, 2026)
Biomass, one of many renewable energy sources, has got increasing attention nowadays, not only for heating application but also for generating electric power. Biomass based gasification power plant is a prospective energy conversion system to be applied for rural area energy sustainability. The present work aims to design and develop, and to performance evaluation of a small-scale biomass gasification power plant with capacity of 5000 watt. The plant consists of a downdraft gasifier, an impinging scrubber, a bio filter, a 5000 watt generator set, and a suction blower. In the present work, the plant is tested using feedstock of rice husk, wood scrap, and blend of rice husk-wood scrap. The gasifier temperature and tar removal by the impinging scrubber is observed and analyzed. The result shows that biomass waste of rice husk, wood scrap, and their blend have a good potential as feedstock of a biomass power plant. The biomass gasification power plant can generate electricity without any problem on the generator set. The water impinging scrubber can be used for tar reduction of the producer gas prior to be supply to the generator set.